A Germination-Specific Endo-β-Mannanase Gene Is Expressed in the Micropylar Endosperm Cap of Tomato Seeds - Nonogaki, Hiroyuki (American Society of Plant Physiologists, 2000)
Endo-β-mannanase (EC 3.2.1.78) is involved in hydrolysis of the mannan-rich cell walls of the tomato (Lycopersicon esculentum Mill.) endosperm during germination and post-germinative seedling growth. Different electrophoretic isoforms of endo-β-mannanase are expressed sequentially in different parts of the endosperm, initially in the micropylar endosperm cap covering the radicle tip and subsequently in the remaining lateral endosperm surrounding the rest of the embryo. We have isolated a cDNA from imbibed tomato seeds (LeMAN2) that shares 77% deduced amino acid sequence similarity with a post-germinative tomato mannanase (LeMAN1). When expressed in Escherichia coli, the protein encoded by LeMAN2 cDNA was recognized by anti-mannanase antibody and exhibited endo-β-mannanase activity, confirming the identity of the gene. LeMAN2 was expressed exclusively in the endosperm cap tissue of tomato seeds prior to radicle emergence, whereas LeMAN1 was expressed only in the lateral endosperm after radicle emergence. LeMAN2 mRNA accumulation and mannanase activity were induced by gibberellin in gibberellin-deficient gib-1 mutant seeds but were not inhibited by abscisic acid in wild-type seeds. Distinct mannanases are involved in germination and post-germinative growth, with LeMAN2 being associated with endosperm cap weakening prior to radicle emergence, whereas LeMAN1 mobilizes galactomannan reserves in the lateral endosperm.